Housing and home unbound intersections in economics, environment and politics in Australia - Cook, Nicole Therese (Routledge, 2016)
"Housing and Home Unbound pioneers understandings of housing and home as a meeting ground in which intensive practices, materials and meanings tangle with extensive economic, environmental and political worlds. Cutting across disciplines, the book opens up the conceptual and empirical study of housing and home by exploring the coproduction of the concrete and the abstract, the intimate and the institutional, the experiential and the collective"--Provided by publisher.